Analysis of the Didactic Act (Between Theory and Practice) - A. Mohamed, Rabah (El Omda in Linguistics and Discourse Analysis, 2021)
The article addresses an attempt to analyze the didactic act, as well as to provide definitions and concepts of some terms related to the teaching–learning process. It also highlights the three components of the didactic triangle and the relationships and interactions that occur among its elements, both in a bilateral and holistic manner at the same time, in order to achieve harmony among its parts. On the knowledge side, the teacher must possess a sufficient knowledge base that enables them to manage the educational process effectively. They should also be familiar with various educational sciences, which can support them during practice and implementation. On the learner’s side, the teacher must have full awareness of the findings of research and studies in psychology, educational psychology, linguistics, sociology, and experimental sciences, in order to use them to understand the learner’s personality from psychological, social, and emotional perspectives. The aim is to quickly detect learning difficulties and imbalances that hinder the learning process, and to find appropriate solutions. Based on this attempt, this article seeks to reveal the nature of the relationships existing between the elements of the teaching act, while also trying to explain the mutual and holistic interactions and tensions among these parties, and the extent of their contribution to the success and activation of the teaching–learning process.